Efficient Level of SEPs Licensing - Gregor Langus; Vilen Lipatov (Center for Economic Studies and ifo Institute (CESifo), 2022)
We study the question whether a holder of standard essential patents (SEPs) should be allowed to choose the level in the value chain at which to offer a FRAND license to its SEPs. We give a pos-itive answer to this question for two reasons. First, the SEP holder and the social planner tend to choose the licensing level that, other things being equal, minimizes transaction costs. Second, the SEP holder maximizes total output, which is often aligned with social welfare maximization by the planner. These two factors make it likely that the SEP holder chooses the efficient level of SET licensing.
Keywords: K21; L40; O34; 330; standard-essential patents; SEP licensing; FRAND; telecommunications; royalty base; licensing level; alignment of incentives